2022
DOI: 10.1371/journal.pgph.0000256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peer-mother interactive programme on prevention of mother-to-child HIV transmission outcomes among pregnant women on anti-retroviral treatment in routine healthcare in Dar es Salaam, Tanzania

Abstract: Peer support services are increasingly being integrated in programmes for the prevention of mother-to-child HIV transmission (PMTCT). We aimed to evaluate the effect of a peer-mother interactive programme on PMTCT outcomes among pregnant women on anti-retroviral treatment (ART) in routine healthcare in Dar es Salaam, Tanzania. Twenty-three health facilities were cluster-randomized to a peer-mother intervention and 24 to a control arm. We trained 92 ART experienced women with HIV to offer peer education, adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
(52 reference statements)
1
9
0
Order By: Relevance
“…Finally, ART attrition was mainly due to the high LTFU of 32% in our cohort, mirroring previous studies from Tanzania and Malawi among women receiving lifelong ART [8,13,41]. While the routine data used lack information on the reasons for LTFU, Ugandan and South African studies that traced LTFU women found that a minority (36% vs. 38%) were receiving ART in other facilities [20,45].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Finally, ART attrition was mainly due to the high LTFU of 32% in our cohort, mirroring previous studies from Tanzania and Malawi among women receiving lifelong ART [8,13,41]. While the routine data used lack information on the reasons for LTFU, Ugandan and South African studies that traced LTFU women found that a minority (36% vs. 38%) were receiving ART in other facilities [20,45].…”
Section: Discussionsupporting
confidence: 82%
“…The higher attrition rates observed in our study could be explained by long waiting times and inadequate services that may lead to reduced defaulter tracing. Task‐shifting using peer mothers can reduce clinic burden and improve ART counselling and retention [41]. ART outreach by community health workers also improves adherence and early defaulter tracing [42].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies were conducted in South Africa (Hamilton et al., 2020; Richter et al., 2014; Rotheram‐Borus et al., 2014); two studies were conducted in Zimbabwe (Orne‐Gliemann et al., 2017; Shroufi et al., 2013), while one study each was conducted in the following regions: Malawi (Phiri et al., 2017), Mozambique (Carlucci et al., 2022), Nigeria (Odiachi et al., 2021), Tanzania (Lyatuu et al., 2022), Uganda (Namukwaya et al., 2015) and Zambia (Simpson et al., 2021). Four studies were conducted at healthcare‐based facilities (Lyatuu et al., 2022; Orne‐Gliemann et al., 2017; Richter et al., 2014; Rotheram‐Borus et al., 2014). There were two studies solely conducted at community‐based facilities (i.e., home) (Hamilton et al., 2020; Simpson et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, mothers with peer-mother support services had a lower ART attrition rate and higher retention in the prevention of motherto-child HIV transmission and ART adherence (Lyatuu et al, 2022;McLeish & Redshaw, 2016;Odiachi et al, 2021;Phiri et al, 2017;Richter et al, 2014;Shroufi et al, 2013;Simpson et al, 2021). Higher retention of participants was found in peer-supported facility-based and peer-supported community-based models with peer-mother support services as compared to healthcare-based standards of care (Phiri et al, 2017).…”
Section: Problems Everything Is Easier Now [Because Of] All the Help ...mentioning
confidence: 97%
See 1 more Smart Citation